CONTEXTUAL ANALYSIS OF QURâ€™AN VERSES IN ENTREPRENEURS - Suharto, Suharto (State Institute of Islamic Studies (IAIN) Palu, 2018)
Implementation of business today can not only use the approach of textual analysis that is in the Qurâ€™an alone, but must enter into the context of contextual analysis in order to interpret the problem in depth so as to form a behavior, which then becomes a habit, to the ultimate culture, and finally into a solid civilization. Based on this, this paper tries to discuss more deeply related to the contextual analysis of Qurâ€™anic verses in entrepreneurship. The end of this article offers the characteristics of business in Islam, namely intentions based on worship, the foundation of Qurâ€™an, sunnah on the basis of belief (tauá¸¥iÌ„d), purpose of the balance of profit world and hereafter (falaÌ„á¸¥), orientation maximization maá¹£laá¸¥ah, high working ethos, character business performer honest (á¹£idq)Â¸ be responsible, trustworthy, tablÄ«gh, professional (faá¹Änah). Capital sourced from á¸¤alaÌ„l property, business scope comply with sharia corridor rules, Free implementation maysir, gharar, ribaÌ„, áº“ulm, baá¹il, zakaÌ„t is an obligation, taxes and CSR is an obligation, vertical business relations (creator) and horizontal (gratitude), final destination of the fulfillment of maqaÌ„á¹£id al-syariÌ„â€™ah (religious, soul, intellectual, descent, and wealth).